Isolated systolic hypertension and its determinants - A cross-sectional study in the adult population of Lucknow district in North India - Midha Tanu; Idris M; Saran R; Srivastava A; Singh S (Wolters Kluwer Medknow Publications, 2010)
Objectives: 1) To determine the prevalence of isolated systolic hypertension (ISH) in the adult population of Lucknow district. 2) To study the determinants of ISH especially the relationship with age. Materials and Methods: A community-based cross-sectional study was conducted in four randomly selected areas of Lucknow district. A total of 800 subjects, aged 20 years and above, 400 from urban and 400 from rural area of Lucknow district were included in the study. The statistical tools used for analysis were Pearson′s Chi-square test and multiple logistic regression. Results: The prevalence of ISH according to JNC-7 criteria was 4.3%, which was 5.1% in men and 3.6% in women. A significant increase in the prevalence of ISH was seen with an increase in age. Multivariate logistic regression analysis of the determinants showed that age, BMI and smoking were significant independent risk factors of ISH. Conclusions: Given the risk of cardiovascular disease associated with ISH, the findings of this study emphasize the need for further research to document the impact of modifiable risk factors of ISH and the effect of hypertension screening and specific health promotion in bringing down the burden of ISH and related cardiovascular morbidity.